Aetiology, epidemiology and clinical characteristics of acute moderate-to-severe diarrhoea in children under 5 years of age hospitalized in a referral paediatric hospital in Rabat, Morocco. Issue 1 (January 2015) - Benmessaoud, Rachid; Jroundi, Imane; Nezha, Mouane; Moraleda, Cinta; Tligui, Houssain; Seffar, Myriam; Alvarez-Martínez, Miriam J.; Pons, Maria J.; Chaacho, Saad; Hayes, Edward B.; Vila, Jordi; Alonso, Pedro L.; et al.
Abstract : The objective of the study was to describe the aetiology, epidemiology and clinical characteristics of the principal causes of acute infectious diarrhoea requiring hospitalization among children under 5 years of age in Rabat, Morocco. A prospective study was conducted from March 2011 to March 2012, designed to describe the main pathogens causing diarrhoea in hospitalized children >2 months and less than 5 years of age. Among the 122 children included in the study, enteroaggregative Escherichia coli (EAEC) and rotavirus were the main aetiological causes of diarrhoea detected. Twelve (9.8 %) children were referred to an intensive care unit, while two, presenting infection by EAEC, and EAEC plus Shigella sonnei, developed a haemolytic uraemic syndrome. Additionally, six (4.9 %) deaths occurred, with EAEC being isolated in four of these cases. Diarrhoeagenic E. coli and rotavirus play a significant role as the two main causes of severe diarrhoea, while other pathogens, such as norovirus and parasites, seem to have a minimal contribution. Surveillance and prevention programmes to facilitate early recognition and improved management of potentially life-threatening diarrhoea episodes are needed. Abbreviations: CRP, C-reactive protein; DAEC, diffusely adherent E. coli ; EAEC, enteroaggregative E. coli ; EHEC, enterohaemorrhagic E. coli ; EIEC, enteroinvasive E. coli ; EPEC, enteropathogenic E. coli ; ETEC, enterotoxigenic E. coli ; HER, Hôpital d'Enfants de Rabat; HUS, haemolytic uraemic syndrome; ICU, intensive care unit; IQR, interquartile range; PCT, procalcitonin; WAZ, weight-for-age Z score.